2016
DOI: 10.1002/psp.2017
|View full text |Cite
|
Sign up to set email alerts
|

Onward Migration as a Coping Strategy? Latin Americans Moving from Spain to the UK Post-2008

Abstract: Research has highlighted that increasing numbers of third-country migrants who have acquired European Union (EU) citizenship in one EU Member State employ the freedom of movement that it provides to onward migrate to other EU destinations. A range of socioeconomic, cultural, and educational factors have been found to drive migrants to move onward to try to fulfil their migration aspirations across multiple locations. This paper suggests that analysing onward migration through the relational lens proposed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0
9

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 14 publications
1
110
0
9
Order By: Relevance
“…Although refugee migrants are less inclined to return back to their country of origin, they might be more likely to move onward as a way of “adjusting” their migration context, as their choice of receiving country may have been made less out of free will. For example, legal integration through the means of acquiring citizenship is used to overcome legal barriers to preferred host countries (Mas Giralt, ; Ortensi & Barbiano di Belgiojoso, ). In a case study of Iranian refugees moving onward from Sweden by Kelly (), onward migration was found to be related to processes of overcoming feelings of displacement and reinforcing personal agency.…”
Section: Onward Migrationmentioning
confidence: 99%
“…Although refugee migrants are less inclined to return back to their country of origin, they might be more likely to move onward as a way of “adjusting” their migration context, as their choice of receiving country may have been made less out of free will. For example, legal integration through the means of acquiring citizenship is used to overcome legal barriers to preferred host countries (Mas Giralt, ; Ortensi & Barbiano di Belgiojoso, ). In a case study of Iranian refugees moving onward from Sweden by Kelly (), onward migration was found to be related to processes of overcoming feelings of displacement and reinforcing personal agency.…”
Section: Onward Migrationmentioning
confidence: 99%
“…Another effect is to trigger the phenomenon of onward migration, whereby already‐present immigrants in a country hit by recession do not return to their home country but move on to another destination. There is a growing literature on the onward migration of third‐country‐origin immigrants in Southern European countries – for example Albanians in Greece onward migrating to the UK (Karamoschou, ), Bangladeshis in Italy also relocating to the UK (Della Puppa and King, ), Latin Americans in Spain moving likewise to the UK (Mas Giralt, ; Ramos, ), and Moroccans in Spain onward migrating to Norway (Jolivet, this issue). In all cases, acquisition of the first host country's citizenship gives the migrants the right to move freely within Europe to the country of their choice.…”
Section: Mobilities and Crisesmentioning
confidence: 99%
“…Previous research has shown that the migration responses of immigrants to economic shocks can be very diverse, varying over time and among individuals (Pandit 1997;Mas-Giralt 2016;Zimmermann and Zaiceva 2012;Czaika 2012;Czaika and de Haas 2012;Pereira 2012;Calnan and Painter 2016). According to the first hypothesis presented in the introduction, we would have expected internal migration to be preferred during the initial stages of the Spanish recession, but once unemployment became endemic, all forms of international emigration increased significantly to become the preferred response among immigrants.…”
mentioning
confidence: 92%
“…Migration responses to the 2008 Spanish financial crisis have generated considerable interest among scholars in this field, with the greatest attention paid to return migration (Cerrutti and Maguid 2016;Recaño and Jáuregui 2014;López de Lera and Pérez-Carames 2015;Recaño, Roig, and de Miguel 2015), followed by remigration (Larramona 2013;Mateos 2015;Pereira 2012;Mas-Giralt 2016). However, with a few exceptions, the changes in internal migration have been largely overlooked (QuinteroLesmes 2016; Bayona-i-Carrasco, Thiers Quintana, and Avila Tàpies 2017).…”
Section: Introductionmentioning
confidence: 99%